Why do we need longitudinal survey data? - Heather Joshi (IZA World of Labor, 2016)
Information from longitudinal surveys transforms snapshots of a given moment into something with a time dimension. It illuminates patterns of events within an individual's life and records mobility and immobility between older and younger generations. It can track the different pathways of men and women and people of diverse socio-economic background through the life course. It can join up data on aspects of a person's life, health, education, family, and employment and show how these domains affect one another. It is ideal for bridging the different silos of policies that affect people's lives.
Keywords: J16; J24; J12; I29; 330; life chances; inequality; mobility; gender; cohort; panel studies